The utilisation of spatial planning in improving urban water culture: a case study of Oranjezicht, Cape Town - Petersen, Gadija Assaa-Imah (School of Architecture, Planning and Geomatics, 2018)
Nothing can exist, live, survive or thrive without water. Water is the basis of life for all living organisms and the centre of life for all societies. The global attitude around water has become territorial as it encompasses an intricate link to the development of nations. Centralising main water supplies beyond urban boundaries may have improved the utilisation of water but has also resulted in the separation of society and water. Water is what gave rise to the city of Cape Town, as there was an abundance of rivers and springs located on and around Table Mountain. This water was first used by the Khoi people and became the reason for colonial settlers residing in the Cape. The City is currently experiencing the worst water crisis in over a century due to increased temperatures and decreased rainfall. Amid the water crisis there appears to be underused, freshwater below Cape Town's CBD, flowing to the Atlantic Ocean via the stormwater reticulation system. This water originates from Table Mountain's rivers, streams and, to an extent, springs. Naturally, the drought has sparked widespread concern for, and attention given to, water and its sustainable usage. This dissertation explores the ways in which the City's water, environmental and spatial planning policies could spark a new and improved water-culture within Cape Town to ensure sustainable, long-term water availability. This is done through investigating the potential of Oranjezicht in becoming a catalytic area for water sustainability due to the locations of the Field of Springs and the Platteklip Stream. This dissertation proposes using water sensitive urban design as well as integrated, collaborative partnerships and management mechanisms to encourage an improved urban water culture.